Beowulf - Mitchell, Stephen, 1948- (New Haven : Yale University Press, 2017)
"Beowulf tells the story of a Scandinavian hero who defeats three evil creatures--a huge, cannibalistic ogre named Grendel, Grendel's monstrous mother, and a dragon--and then dies, mortally wounded during his last encounter. If the definition of a superhero is "someone who uses his special powers to fight evil," then Beowulf is our first English superhero story, and arguably our best. It is also a deeply pious poem, so bold in its reverence for a virtuous pagan past that it teeters on the edge of heresy. From beginning to end, we feel we are in the hands of a master storyteller. Stephen Mitchell's marvelously clear and vivid rendering re-creates the robust masculine music of the original. It both hews closely to the meaning of the Old English and captures its wild energy and vitality, not just as a deep "work of literature" but also as a rousing entertainment that can still stir our feelings and rivet our attention today, after more than a thousand years. This new translation--spare, sinuous, vigorous in its narration, and translucent in its poetry--makes a masterpiece accessible to everyone." -- Publisher's description.
Introduction -- About This Translation -- About the Text -- A Note on Pronunciation -- Map: The Geography of Beowulf -- Beowulf -- Appendix: Genealogical Tables -- Notes -- Bibliography -- Acknowledgments.
Inlcudes bibliographical references and index.
Print version record.
Parallel text on facing pages in Anglo-Saxon (Old English) and English.
JSTOR
Keywords: Beowulf, -- King of the Geats -- Poetry; Grendel -- (Monster) -- Poetry; Beowulf; Beowulf, -- King of the Geats; Grendel -- (Monster); Beowulf; Dragons -- Poetry; Heroes -- Poetry; Epic poetry, English (Old); Scandinavia -- Poetry; Héros -- Poésie.; Dragons -- Poésie.; Poésie épique anglaise (vieil anglais); Scandinavie -- Poésie.; FICTION -- Literary; Dragons; Epic poetry, English (Old); Heroes; Scandinavia; Epic poetry; Poetry; Epic poetry; Poésie épique.